2013
DOI: 10.1149/05301.0185ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Photoluminescence Efficiency of Germanium Dots Self-Assembled on Oxides

Abstract: Self-assembled Ge quantum dots were formed by in-situ thermal annealing of a thin amorphous Ge layer deposited by molecular beam epitaxy either on a thin porous TiO 2 layer grown on SiO 2 on Si(001) or directly on the SiO 2 layer itself. For samples with dot diameters ranging from 10 to 35 nm, the dot photoluminescence (PL) appeared primarily as a wide near-infrared band peaked near 800 meV. The peak energy of the PL band reflects the average dot size and its shape depends on the dot size distribution. Using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Theoretical studies have suggested E G ∼ D −x , where 1 ≤ x ≤ 2 and D is the NS diameter 3,7,10 , which has been demonstrated experimentally 3,11,12 . In this work, we theoretically elucidate the dimensional dependence (D-dep) for Ge quantum dots (QDs) using experimental results reported previously by Lockwood et al 13 . We find that above D ≈ 6 nm the QDs behave like E G ∼ D −1 , below which E G ∼ D −2 .…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies have suggested E G ∼ D −x , where 1 ≤ x ≤ 2 and D is the NS diameter 3,7,10 , which has been demonstrated experimentally 3,11,12 . In this work, we theoretically elucidate the dimensional dependence (D-dep) for Ge quantum dots (QDs) using experimental results reported previously by Lockwood et al 13 . We find that above D ≈ 6 nm the QDs behave like E G ∼ D −1 , below which E G ∼ D −2 .…”
Section: Introductionmentioning
confidence: 99%
“…in light-emitting diodes or lasers, the k-selection rule that forbids optical dipole transitions at the minimum band gap of Ge has to be broken. To this end, ingenious approaches have been proposed, for instance, based on straining [10], nanostructuring [11,12], or amorphization [13].…”
Section: Introductionmentioning
confidence: 99%
“…Good qualitative agreement was obtained between the PLderived dot size distributions and those from AFM. Further work showed a nonlinear increase in the PL efficiency with decreasing dot diameter, suggesting that dot PL spectra used in conjunction with the theory provided a promising method to evaluate Ge dot size distributions [59]. The latter approach confirms that oxide nanoperforated surfaces with controlled motif dimension and periodicity can be used to control the size of metallic Ge nanodots formed by solid dewetting.…”
Section: Nanomasks For Controlled Solid Dewetting Of Semiconductor Namentioning
confidence: 72%